Midwall Fibrosis and Cardiac Mechanics: Rigid Body Rotation Is a Novel Marker of Disease Severity in Pediatric Primary Dilated Cardiomyopathy - Al-Wakeel-Marquard, Nadya; Seidel, Franziska; Kühnisch, Jirko; Kuehne, Titus; Berger, Felix; Messroghli, Daniel R.; Klaassen, Sabine (Frontiers in Cardiovascular Medicine, 2022)
Background Midwall fibrosis (MWF) detected by late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) predicts adverse outcome in adults with dilated cardiomyopathy (DCM). Its relevance in children and adolescents is relatively unknown. Left ventricular (LV) strain, rotation and twist are important parameters of cardiac function; yet, their role in pediatric heart failure is understudied. This study aimed to evaluate MWF and cardiac mechanics in pediatric DCM. Methods Patients ≤21 years with primary DCM were prospectively enrolled and underwent standardized CMR including LGE. All participants were categorized according to the presence or absence of MWF (MWF+ vs. MWF–). Cardiac mechanics were assessed using CMR feature tracking. Impaired LV twist with apex and base rotating in the same direction was termed rigid body rotation (RBR). Results In total, 17 patients (median age 11.2 years) were included. MWF was present in seven patients (41%). Median N-terminal pro brain natriuretic peptide (NT-proBNP) was higher (5,959 vs. 242 pg/ml, p = 0.887) and LV ejection fraction (LVEF) lower (28 vs. 39%, p = 0.536) in MWF+ vs. MWF– patients, yet differences were not statistically significant. MWF+ patients had reduced global longitudinal (GLS), circumferential (GCS) and radial strain (GRS), again without statistical significance (p = 0.713, 0.492 and 1.000, respectively). A relationship between MWF and adverse outcome was not seen (p = 0.637). RBR was more common in MWF+ (67 vs. 50%), and was associated with the occurrence of adverse events (p = 0.041). Patients with RBR more frequently were in higher New York Heart Association classes (p = 0.035), had elevated NT-proBNP levels (p = 0.002) and higher need for catecholamines (p = 0.001). RBR was related to reduced GLS (p = 0.008), GCS (p = 0.031), GRS (p = 0.012), LV twist (p = 0.008), peak apical rotation (p < 0.001), and LVEF (p = 0.001), elevated LV end-diastolic volume (p = 0.023) and LV end-systolic volume (p = 0.003), and lower right ventricular stroke volume (p = 0.023). Conclusions MWF was common, but failed to predict heart failure. RBR was associated with clinical and biventricular functional signs of heart failure as well as the occurrence of adverse events. Our findings suggest that RBR may predict outcomes and may serve as a novel marker of disease severity in pediatric DCM. Clinical Trial Registration:https://clinicaltrials.gov/, identifier: NCT03572569.